Feminists’ interpretation of the selected verses of the Qur’an regarding woman’s empowerment and right: a contextual approach - Ali, Md. Yousuf (Zes Rokman Resources, 2016)
The interpretation of the verses of the Qur’Én regarding women’s empowerment and right is a challenging and debatable issue. In Islam, the Qur’Én is seen by almost all Muslims as the words of Allah (swt). The majority Muslim exegetes used the method of literal reading while Muslim feminists applied the methods of the contextual and historical readings towards understanding wmoen’s empowerment and their right in society. Muslim feminists obviously cannot reject or question the text itself but they have to take the Qur’Én in its entirety. The contextual and historical readings applied by Muslim feminists involve reading a verse with regard to the historical, social, and political context in which it was revealed in order to disclose an underlying liberal intent. The aim of it is to liberate Muslims from a literal reading of the Qur’Én. Such method by Charles Kurzaman is considered as the liberal SharÊÑah approach.ii This approach argues that women have the similer right and the authority of empowerment in every aspect of life as mn has. However, Muslim feminists face great challenges and accusations made by traditional Muslim exegetes and antifeminists because feminist scholarship is not loyal to the teachings of Islam and denies its heritage. Such approach also produces liberal Islam and liberal SharÊÑah, influenced by Western values and imposed upon Islam and Muslims as believed by anti-feminists. Given the context, this study examines women’s empowerment and right according to the selected verses of the Qur`an interpreted by the Muslim feminists. This also focuses on Muslim women’s engagement in developing the feminism and exegetes’s approaches to the tafsir al-Qur`an about women’s empowerment and their right. This also analyzes contextual approaches applied by Muslim feminists to interpret the contentious verses about women’s leadership and their rights within the purview of contemporary thought which is based on the textual arguments of the Qur’Én and Sunnah. Two questions on the basis of those verses will be examined; one is the question of intra-textual and contextual approaches to women’s empowerment and the second is their rights in present context. The study concludes that though there are accusations against Muslim feminists, but the majority of the Muslim scholars has viewed women’s rights as their innate-rights and with a textual analysis and inductive approach they have made the prospects of formulating an Islamic stance on the basis of the sacred texts of the Qur’Én in the current context.